Automated System Design for Sending Arrival Messages at Backup Facilities in Jakarta Air Traffic Service Center - Akbar, Muhammad Caesar; Amren, Hairul; Saputra, Surya Tri; Abimanyu, Yuda (Politeknik Penerbangan Indonesia Curug, 2025)
This research is urgent to ensure that the Arrival Message Engine, which is separate from the Main ATC System, can send ATS Messages automatically. This was deemed necessary to do immediately to back up a bug in the Main ATC System, which caused several Arrival Messages not to be sent. The method used is the research and development method, meaning it is a scientific way to research, design, and test the validity of the product that has been created. Research and development has four levels: researching without testing, testing without researching, researching and testing to develop existing products, and researching and testing to create new products. A product has been produced in the form of an arrival message delivery automation system that automatically sends arrival message data to the AFTN message network and can run well per the user needs assessment in this research. It was proven from the design validation results that the test results were 100% and categorized as very feasible, as well as from the system test results using the Black Box method. As a continuation of this research, a warning and monitoring system for sending ATS messages is needed when a failure or anomaly occurs in the main system. It is hoped that this research can be considered for use in operations as an alternative facility so that it can support activities related to handling ATS messages or flight data processing systems in flight navigation operations.